Influence of the COVID-19 pandemic on the prevalence of depression in U.S. adults: evidence from NHANES - Yun Jiang; Wusheng Deng; Mei Zhao (Scientific Reports)
Abstract The impact of the COVID-19 pandemic on the epidemiological characteristics of depression among adults in the U.S. remains unclear. This study aims to analyze trends in depression prevalence over time and quantify the effect of the COVID-19 pandemic on its prevalence. Using data from 2007 to 2023 provided by the National Health and Nutrition Examination Surveys (NHANES), this study examined 36,472 participants. Results revealed an increasing trend in depression prevalence among U.S. adults from 2007 to 2023. Notably, the overall weighted prevalence of depression following the COVID-19 pandemic (12.4%, 95% CI: 10.6-14.1%) was significantly higher than in all years prior to the pandemic. Subgroups such as females, Mexican Americans, and young adults experienced particularly pronounced increases. By analyzing data from two survey cycles close to the onset of the COVID-19 outbreak, the study identified a significant impact of the pandemic on depression prevalence, with an adjusted odds ratio of 1.58 (95% CI: 1.28–1.94). Individuals with lower socioeconomic status and those without pre-existing conditions exhibited greater increases in depression prevalence, whereas the emotional health of individuals who smoke appeared unaffected by the pandemic.